Micropropagation of Ruscus aculeatus L. - Khiêm, Đinh Văn; Cương, Hoàng Văn; Thanh Hằng, Nguyễn Thị; Huyên, Phan Xuân; Phượng Hoàng, Nguyễn Thị (Vietnam Journal of Biotechnology, 2018)
Ruscus aculeatus L. is a small evergreen perennial species, is commonly used either as medicinal or ornamental plant thanks to its evegreen long-lasting branches. Currently, the species is endangered by population redutions due to habitat alteration, the lack of seed production caused by pollination failure and also because of the intense harvesting for medicical uses or for floral bouquets. Micropropagation opens new directions for its ex situ conservation, as well as to generate large scale material for natural population reinforcement or for commercial purposes. In this study, effects of BA, NAA and coconut water on shoot regeneration, IBA on root formation of Ruscus aculeatus L., and type of substrates on acclimatization and growth of seedlings were investigated. The results showed that ½MS medium supplemented with 4 mg/l BA, 0.5 mg/l NAA and 15% (v/v) coconut water, 30 g/l sucrose, and pH 5.8 was the most suitable for shoot regeneration of Ruscus aculeatus L. in vitro (20.2 shoots, shoot length of 6.0 cm). Root formation of Ruscus aculeatus L. was optimal on ½MS supplemented with 1.5 mg/l IBA, 30 g/l sucrose, and pH 5.8 (frequency of rooting 100%, shoot length of 1.9 cm with 16.66 roots per seedling). Finally, the sufficiently rooted plantlets were transferred to greenhouse for hardening. After 2 months, coconut fiber substrate was the most suitable for seedling growth and development (with survival rate of 85%, root number of 8.7 and shoot length of 7.6 cm). We have developed protocol for the rapid micropropagation of Ruscus aculeatus L. in order to create a large number of seedlings for commercial production.